Incapacitating solar urticaria: successful treatment with omalizumab - Katarina Kieselova; Felicidade Santiago; Martinha Henrique (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Solar urticaria is a rare form of physical urticaria mediated by immunoglobulin E. The lesions appear immediately after the sun exposure, interfering with the patient's normal daily life. Omalizumab, a monoclonal anti-IgE antibody, has been recently approved for the treatment of chronic spontaneous urticaria, and the latest reports support its role also in the treatment of solar urticaria. Hereby, we report a case of solar urticaria refractory to conventional treatment strategies, with an excellent response to treatment with omalizumab and phototesting normalization.